Detecção de anticorpos anti-Toxoplasma gondii em cavalos carroceiros da região metropolitana de Curitiba, Paraná, Brasil - Finger, Mariane Angélica; Villalobos, Eliana Monteforte Cassaro; Lara, Maria Do Carmo Custódio De Souza Hunold; Cunha, Elenice Maria Sequetin; Filho, Ivan Roque de Barros; Deconto, Ivan; Dornbusch, Peterson Triches; Ullmann, Leila Sabrina [UNESP]; Biondo, Alexander Welker (My University, 2012)
Toxoplasma gondii, the agent for toxoplasmosis, has worldwide distribution. Horses normally play a secondary role in its life cycle, but movement around urban areas, feeding on grass and the increasing use of carthorses for gathering recyclable material in some urban areas of Brazil may increase their exposure to T. gondii infection. The aim of the present study was to investigate the frequency of anti-T. gondii antibodies in carthorses in the metropolitan region of Curitiba, PR. IgG antibodies against T. gondii were detected using the indirect fluorescence antibody test (IFAT) (titers ≥ 64). Seventeen (17.0%) of the 100 horses sampled were seropositive. There were no statistical differences in relation to sex (p = 0.28) or age (p = 0.15). Our findings suggest that carthorses are exposed to T. gondii infections and that no associations with age or sex exist.
Detection of anti-Toxoplasma gondii antibodies in carthorses in the metropolitan region of Curitiba, Paraná, Brazil
Keywords: Carthorses; Indirect fluorescence antibody test; Toxoplasma gondii